Optimizing Household Economic Resource to Lessen Population Pressures on Villages around Kerinci Seblat National Park Bengkulu Province - Ketut Sukiyono; Septri Widiono (Institut Pertanian Bogor (IPB University), 2020)
Villages around Kerinci Seblat National Park (Taman Nasional Kerinci Seblat, TNKS) have experienced population pressure. This condition which if not addressed immediately will encourage the community around the TNKS to enter and encroach the forest to meet their household needs. This is getting worse along with the finding that the community around TNKS also does not have many alternative sources of income. For this reason, designing strategies for optimizing household economic to lessen population pressures are noteworthy. Focus group discussion (FGD) and analysis hierarchy process (AHP) was applied to design and to determine development strategy for household economic empowerment and twenty-five key informants including fifteen farmer households were interviewed. The AHP results conclude that the production aspect is the most important that needs to be given priority in the development of plantation production. This conclusion is based on its highest relative priorities (weights), i.e., 0.298. Of the three programs identified and using weight result of AHP, community seed assistance is the most important program in the development of plantation production (weight of 0.494). The seed assistance program is the most important compared to providing soft loans (weight of 0.29) and expanding to production inputs accessibility (weight of 0.216). Meanwhile, human resource development aspects are the most attractive strategy for food crop production development, especially rice, with a weight of 0.325. Aspects of human resource development are more focused on improving farmer knowledge in cultivation than marketing and post-harvest handling aspects. Optimization of pekarangan resources is directed to the development of the chicken farm (weight = 0.274) focused on improving the production aspect (weight = 0.328). Among three priority programs, day-old chicken assistance (weight = 0.512) is more needed than access to soft loans (weight = 0.242) and feed programs (weight = 0.246).